EFEK UKURAN, WAKTU PEMANASAN DALAM PERTUMBUHAN DAN PERKEMBANGAN BAWANG PUTIH (Allium sativum L) SECARA INKONVENSIONAL - Asih K. Karjadi; Nurmalita Waluyo; Neni Gunaeni (UIN Sunan Gunung Djati Bandung, 2023)
Garlic (Allium sativum L.) is included in the genus Allium sp., propagated vegetatively through clove. In plants that are propagated vegetative, viral systemic diseases will be carried over to the next generation. In conventional methods/ tissue culture techniques combined with size and heat treatment the explant material can used as virus elimination. The activity research conducted at the Balitsa tissue culture laboratory from April to July 2018. The purpose of the study was to see the effect of size, heat treatment of explant material on the growth and development of garlic variety Tawang Mangu. The treatments were (1) explant size E1 = 1/3 clove, E2 = shoot tip, E3 = meristem tissue, (2) heat treatment 37oC, T1 = without treatment, T2 = heat treatment for 2 weeks, T3 = heat treatment for 4 weeks, T4 = heat treatment 6 weeks. The composition of the growing media: MS + MS vits + sucrose 30 g/l + IAA 2 mg/l +Kinetin 2 mg/l + GA3 0.01 mg/l + Gel gro 2 g/l, pH 5.7. The results of the study (1) were visually observed that the smaller the size of the explants and the length of heat treatment, the lower the percentage of explants that grew normally. (2) Percentage of contamination 33.33 – 60% caused by bacteria or fungi. (3) The percentage of infected plantlet with virus with DAS ELISA technique were 40 – 66.67%.